Targeting LRP/LR for the prevention of tumour formation and metastasis in lung cancer models - Bignoux, Monique (My University, 2022)
The incidence and mortality rates of cancer are growing rapidly worldwide, with lung cancer being the most commonly occurring cancer in males. One of the most important considerations in the development of therapeutics for lung cancer is that of early detection and diagnosis, as thereafter, treatments become less effective and later malignant stages become fatal. However, in South Africa, the probability of early diagnosis is extremely low and thus the focal point is the need for effective mechanism-based targeted therapies for the treatment of lung cancer. Cancer is a multi-step process characterised by the hallmarks of cancer and their enabling characteristics. The 37 kDa /67 kDa laminin receptor (LRP/LR) is predominantly a cell surface receptor but also acts intracellularly and is known to be overexpressed in various cancer types. LRP/LR plays a role in numerous cancer hallmarks, including metastasis, angiogenesis, cell viability maintenance, apoptotic evasion and mediating telomerase activity. In this context, LRP/LR provides a putative target for the treatment of multiple cancer hallmarks. Furthermore, the knockdown of LRP/LR with LRP-specific siRNA technology significantly impedes adhesion and invasion, induces apoptosis and impedes telomerase activity in vitro. Therefore, this current study included an investigation into the effect of downregulating LRP/LR with LRP-specific siRNA on reducing cell viability, migration potential, telomerase activity as well as inducing apoptosis in A549 lung cancer cells. The A549 cells exhibited a significant decrease in cell viability, migration potential and telomerase activity, as well as a significant increase in apoptosis after downregulation of LRP/LR. Proteomics analysis further suggested the re-establishment of immune control over the lung cancer cells, a novel facet to LRP downregulation in cancer. This therefore indicates that the approach to target LRP/LR is a potentially powerful treatment against multiple cancer hallmarks. However, it is not feasible to use ‘naked’ siRNA molecules in vivo and therefore, an efficient delivery system is required. For this, siRNA can be encapsulated in polymeric polylactic-co-glycolic acid (PLGA), which enables the siRNA to more readily be taken up by cells. Therefore, this current study also included assessing PLGA nanoparticles as a potential delivery vehicle for LRP-specific siRNA. PLGA nanocapsule production was optimised for uniformity and size, thereafter HEK293 and A549 lung cancer cells were treated with varying concentrations of empty PLGA nanoparticles and showed no significant decrease in cell viability or LRP/LR levels when treated with 1-5% empty PLGA nanoparticles for 72 hours. Therefore, signifying that the PLGA nanocapsules are favourable for use as a delivery system.
A thesis submitted in fulfilment of the requirements for the degree of Doctor of Philosophy to the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand, Johannesburg, 2022